Targeting thyroid cancer with acid-triggered release of doxorubicin from silicon dioxide nanoparticles - Li SJ (Dove Medical Press, 2017)
Shijie Li,1 Daqi Zhang,1 Shihou Sheng,2 Hui Sun1 1Department of Thyroid Surgery, 2Department of Gastrointestinal Colorectal and Anal Surgery, China–Japan Union Hospital of Jilin University, Chang Chun, People’s Republic of China Abstract: Currently, therapy for thyroid cancer mainly involves surgery and radioiodine therapy. However, chemotherapy can be used in advanced and aggressive thyroid cancer that cannot be treated by other options. Nevertheless, a major obstacle to the successful treatment of thyroid cancer is the delivery of drugs to the thyroid gland. Here, we present an example of the construction of silicon dioxide nanoparticles with thyroid–stimulating-hormone receptor-targeting ligand that can specifically target the thyroid cancer. Doxorubicin nanoparticles can be triggered by acid to release the drug payload for cancer therapy. These nanoparticles shrink the tumor size in vivo with less toxic side effects. This research paves the way toward effective chemotherapy for thyroid cancer. Keywords: thyroid cancer, silicon dioxide nanoparticle, doxorubicin, acid-triggered release